An interdisciplinary framework examining culture and adaptation in migrant children and adolescents. Issue 176 (17th March 2021) - Pérez, Isabela E.; Wu, Rachel; Murray, Carolyn B.; Bravo, Diamond
Abstract: With increasing rates of globalization, understanding the cultural factors that promote positive adaptation in migrant children and adolescents is vital. In prior research, acculturation and enculturation frameworks often rely on unidimensional or bidimensional conceptions of culture to study the effects of migration on child and adolescent development. However, the contemporary strategies that migrant children and adolescents utilize to navigate multicultural contexts remain undertheorized. Therefore, we advance an interdisciplinary framework that describes the factors and processes that affect migrant child and adolescent development across four contexts: global, macrosystem, microsystem, and the individual level. Additionally, conceptualizations of cultural adaptation are broadened in our framework by examining the intersections of community cultural wealth, cultural preservation, and cultural restoration. We highlight the importance of prioritizing the culture and experiential knowledge of migrant children and adolescents in the development of policy, research, and practice, to support their positive adaptation in a globalized society.